Implementasi Peraturan Gubernur No 62 Tahun 2023 tentang Manajemen Talenta Aparatur Sipil Negara di Badan Kepegawaian Provinsi Jawa Timur - Novia Agustyas Putri; Indah Prabawati; Tjitjik Rahaju; Tauran T (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to analyze the implementation of Talent Management policies at the Regional Civil Service Agency (BKD) of East Java Province, based on Governor Regulation Number 62 of 2023 concerning Talent Management. Talent management is a key pillar in the merit system transformation to produce competent and competitive civil servants. However, the transition from a conventional system to a digital talent-based system requires complex structural and behavioral readiness. This study uses a descriptive qualitative approach, utilizing George C. Edwards III's policy implementation theory, which consists of four main variables: Communication, Resources, Disposition, and Bureaucratic Structure. The results indicate that Talent Management implementation at the East Java Regional Civil Service Agency (BKD) has been effective but still faces several technical challenges. In terms of communication, information transmission has been carried out extensively through the Si-Master system, although information clarity at the regional apparatus level far from the center of government still needs to be improved. In terms of resources, the availability of digital infrastructure and a capable Assessment Center are key supports, but the number of certified assessors remains limited compared to the civil servant population. The Disposition variable indicates strong support from leadership, driven by incentives in the form of career certainty for high-performing civil servants. Meanwhile, in the bureaucratic structure, the use of digital SOPs has successfully minimized fragmentation between sectors, thus making the process of mapping ASN into the 9-box matrix more transparent and accountable. This study concludes that the integration of the four Edwards III variables into the digital platform is key to the success of the East Java Regional Civil Service Agency (BKD) in implementing an objective succession plan.